PENGARUH EVALUASI TES FORMATIF TERHADAP HASIL BELAJAR MATEMATIKA DITINJAU DARI TINGKAT KEMANDIRIAN BELAJAR MAHASISWA STT-PLN JAKARTA DENGAN MENGGUNAKAN ANALISIS VARIAN ANOVA - Dwi Anggaini; Miftahul Fikri; Denny Setiawan (Sekolah Tinggi Teknik - PLN, 2018)
Research is a study that aims to find out the truth by researching and analyzing the influence of student learning independence in formative tests on student mathematics learning outcomes. The study was conducted at the Technical High School - PLN Jakarta in the even semester of 2017/2018 school year with a sample of 52 students using cluster random sampling technique. To retrieve data using questionnaire instruments to capture data on student learning independence variables and use tests to measure students' mathematics learning outcomes. Data analysis was performed using one-way ANOVA to prove the validity of the research hypothesis. Based on the results of the data analysis test, it can be concluded that there is an interaction between formative tests and students' learning independence towards mathematics learning outcomes and is directly proportional to learning independence.